INTEGRASI NILAI QANA’AH DALAM LAYANAN BIMBINGAN KONSELING ISLAM UNTUK MEREDUKSI FOMO PADA REMAJA PENGGUNA TIKTOK - Salma Kusuma Listiani; Lathifatus Sa Diyyah; Rahmi Anekasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Fear of Missing Out (FoMO) phenomenon among adolescent TikTok users is increasing along with the intensity of social media use. FoMO arises from the urge to constantly follow trends, gain social validation, and compare oneself to others, resulting in anxiety, stress, low self-acceptance, and decreased psychological well-being. This study aims to examine the integration of the value of contentment (qana'ah) in Islamic Guidance and Counseling (BKI) services as an effort to reduce FoMO in adolescent TikTok users. The study used a qualitative approach with library research. Data were obtained through a review of various scientific journals, articles, and relevant literature discussing FoMO, TikTok, contentment (qana'ah), and Islamic Guidance and Counseling. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results show that the integration of the value of contentment (qana'ah) in BKI services can be an effective psychospiritual approach to reducing FoMO. The value of contentment, which includes attitudes of gratitude, patience, contentment, and feeling self-sufficient, helps adolescents improve self-control, reduce dependence on social validation, and strengthen mental resilience in the digital era. The qana'ah integration model is implemented through assessment, intervention, and evaluation stages, utilizing strategies of self-reflection, spiritual reframing, and Islamic digital literacy. Thus, the integration of qana'ah in the Islamic Education and Training Center (BKI) contributes to improving adolescents' psychological well-being in a more holistic and sustainable manner. Fenomena Fear of Missing Out (FoMO) pada remaja pengguna TikTok semakin meningkat seiring intensitas penggunaan media sosial yang tinggi. FoMO muncul akibat dorongan untuk terus mengikuti tren, memperoleh validasi sosial, dan melakukan perbandingan diri dengan orang lain, sehingga berdampak pada kecemasan, stres, rendahnya penerimaan diri, serta menurunnya kesejahteraan psikologis remaja. Penelitian ini bertujuan untuk mengkaji integrasi nilai qana’ah dalam layanan Bimbingan Konseling Islam (BKI) sebagai upaya mereduksi FoMO pada remaja pengguna TikTok. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data diperoleh melalui kajian berbagai jurnal ilmiah, artikel, dan literatur relevan yang membahas FoMO, TikTok, qana’ah, dan Bimbingan Konseling Islam. Analisis data dilakukan menggunakan teknik content analysis melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa integrasi nilai qana’ah dalam layanan BKI dapat menjadi pendekatan psikospiritual yang efektif untuk mengurangi FoMO. Nilai qana’ah yang meliputi sikap syukur, sabar, ridha, dan merasa cukup mampu membantu remaja meningkatkan kontrol diri, mengurangi ketergantungan terhadap validasi sosial, serta memperkuat resiliensi mental di era digital. Model integrasi qana’ah diterapkan melalui tahapan asesmen, intervensi, dan evaluasi dengan strategi muhasabah, reframing spiritual, dan literasi digital Islami. Dengan demikian, integrasi qana’ah dalam BKI berkontribusi terhadap peningkatan kesejahteraan psikologis remaja secara lebih holistik dan berkelanjutan.